A qualitative study on the challenges of clinical leadership in an HIV care system: insights from healthcare providers in Eldoret, Kenya - Cherop, Felishana; Korir, Michael; Bagire, Vincent; Kimwolo, Andrew; Naanyu, Violet; Wachira, Juddy (Frontiers in Health Services, 2025)
IntroductionThe provision of quality services to patients in healthcare facilities requires effective clinical leaders who will transcend their technical expertise and coordinate and direct patient care through clinical leadership roles. Clinical leadership refers to using clinical experience to provide direction, inspire and promote values and vision, and promote quality clinical care. However, there is a limited understanding of the challenges faced by clinical leaders within HIV care systems in Kenya. This study explored the views of healthcare providers on clinical leadership challenges in HIV care highlighting the sources and consequences.MethodsWe conducted an exploratory qualitative study between December 2019 to May 2020 marked by COVID-19 involving (n = 22) healthcare providers who were purposively sampled to participate in in-depth interviews in the AMPATH-MTRH HIV facility in Eldoret, Kenya. Ethics approval was granted, and participants consented to participation and audio-recorded interviews. All data that were collected from participants were de-identified and kept in a confidential format to protect participant anonymity. A thematic analysis approach was used to analyze data and Nvivo v.12 software was used for data management.ResultsParticipants identified three broad themes that described clinical leader challenges in an HIV facility including (1) supply-side challenges, a shortage of resources, staff welfare, and team dynamics; (2) demand-side challenges, unmet patient expectations, lack of appreciation by the patients, lack of additional gains and incentives, financial constraints, and stigma; (3) health system challenges, rigid health system structure, lack of management support, unavailable services in the facility. These challenges negatively impacted healthcare providers' performance including clinical leaders', compromised patient care, and created inefficiencies in the HIV care system.ConclusionThe results provided important insights from the perspectives of healthcare providers. They show that in HIV care systems, clinical leaders are faced with diverse challenges that emerge from the supply, demand, and health system sides that affect patient care and system performance. Healthcare system leaders can strengthen management support systems and leadership training for clinical leaders to improve HIV care provision as well as provide career growth opportunities for clinical leaders to maximize their expertise in improving HIV care and system performance.